ON THE PROSPECTS OF CAGE AQUACULTURE IN THE TUYABUGUZ RESERVOIR (UZBEKISTAN) - Kim S. I. (Modern American Journals, 2025)
In recent decades, the increase in fish production in the world has occurred due to aquaculture - cultivation in artificial conditions. All this is very relevant for Uzbekistan, where there is practically no commercial fishing and fish production is carried out mainly in ponds [2].